2006
DOI: 10.1186/1471-2334-6-66
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of the ELISPOT test after treatment in Gambian tuberculosis cases

Abstract: Background: New tools are required to improve tuberculosis (TB) diagnosis and treatment, including enhanced ability to compare new treatment strategies. The ELISPOT assay uses Mycobacterium tuberculosis-specific antigens to produce a precise quantitative readout of the immune response to pathogen. We hypothesized that TB patients in The Gambia would have reduced ELISPOT counts after successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 15 publications
(14 reference statements)
10
86
1
Order By: Relevance
“…A correlation between antigen load and the extent of IFN-␥ secretion in response to ESAT-6 and CFP-10 has been observed both in experimental systems and in humans (33)(34)(35). Further evidence in favor of this relationship comes from observations that demonstrate a falling response during successful chemotherapeutic treatment (3,33,36). The bacillary burden in LTBI is many logs lower than in active disease and so it may not be possible to conclude with confidence that a negative IFNGRA excludes LTBI.…”
Section: Discussionmentioning
confidence: 91%
“…A correlation between antigen load and the extent of IFN-␥ secretion in response to ESAT-6 and CFP-10 has been observed both in experimental systems and in humans (33)(34)(35). Further evidence in favor of this relationship comes from observations that demonstrate a falling response during successful chemotherapeutic treatment (3,33,36). The bacillary burden in LTBI is many logs lower than in active disease and so it may not be possible to conclude with confidence that a negative IFNGRA excludes LTBI.…”
Section: Discussionmentioning
confidence: 91%
“…This molecule also exists in bacillus Calmette-Guerin (BCG) vaccine, with expression quantity 10 times higher than that of BCG [3] . The antigen contains seven antigenic epitopes and can induce humoral and cellular immune responses and be used for serological diagnosis of TB.…”
Section: Relevant Antigens Of Humoral Immunity Against Mtbmentioning
confidence: 99%
“…As a fibronectin-binding protein, Ag85 exists in higher amounts of serum of patients with active TB in comparison with patients with non-active TB or other lung diseases or healthy controls [2] . In the study among indigenous people of Mexico, Abebe et al [3] proved that IgG exhibits good effect on Mtb complex Ag85. Another study showed that compared with patients cured by anti-TB treatment, effective antibody titer was more remarkable for Ag85 in non-cavernous TB.…”
Section: Relevant Antigens Of Humoral Immunity Against Mtbmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the hypothesis that the IFN-␥ ELISpot assay could function as a bacterial load sensor, a comparatively smaller amount of SFCs in response to ESAT-6 and/or CFP-10 over time would be indicative of a good response to treatment, leading to a lower probability of relapse. Though encouraging, the readings of recent exploratory studies were confounded by immune status, stage of infection, and previous drug treatment; and no clear conclusion was reached with regard to the predictive value of the ELISpot assay as a marker of therapy response (1,5,13,19,28). Relapse as a clinical trial endpoint is a key issue in drug development.…”
mentioning
confidence: 99%